A Comparison of the functional results between the conservative treatment and the surgical use of the locking plate in the management of the comminuted fractures of the proximal end of the humerus. - عروس, علي; غياث حلوم; عزة المحمد (Latakia University Journal -Medical Sciences Series, 2023)
Objective: to evaluate the functional outcomes and the development of complications after both conservative and surgical treatments of the comminuted fractures of the proximal end of the humerus. Patients and methods: A retrospective study included 40 adult patients above the age of 18 years old. The patients were divided into two groups (conservative and surgical). Constant & Murley performed after 1 year after treatment. The duration of the research was two years, from March 2019 to March 2021. Results: There were no statistically differences between the two groups according to Constant & Murley index. The complications rate was higher in the first group (conservative). Conclusion: considering the high incidence and the high complications rate of comminuted proximal humerus fractures, we recommend subjecting patients sustaining a physical therapy for a better functional results. We also recommend surgical treatment for young and athletic patients to reduce the incidence of movement restriction, and to speed up their return to pre-injury activity levels. We also recommend conservative treatment for old and non-surgical candidates patients to reduce the complications of surgery. Keywords: Humerus, Conservative, Plate, Comminuted, Functional.